2012
DOI: 10.1158/1535-7163.mct-12-0101-t
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGF-β Enhances the In Vivo Antitumor Efficacy of EGF Receptor–Targeted Therapy

Abstract: EGF receptor (EGFR)–targeted monoclonal antibodies (mAb), such as cetuximab, execute their antitumor effect in vivo via blockade of receptor–ligand interactions and engagement of Fcγ receptors on immune effector cells that trigger antibody-dependent cell-mediated cytotoxicity (ADCC). We show that tumors counteract the in vivo antitumor activity of anti-EGFR mAbs by increasing tumor cell-autonomous expression of TGF-β. We show that TGF-β suppresses the expression of key molecular effectors of immune cell–mediat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 41 publications
2
62
1
1
Order By: Relevance
“…In addition, the targeting of EGFR signaling by the EGFR antibody Cetuximab in a xenograft model of head and neck cancer resulted in emergence of resistant tumor cells that expressed relatively higher levels of TGFb and elevated levels of TGFb in the tumor microenvironment enable tumor cells to evade antibodydependent cell-mediated cytotoxicity and resist the antitumor activity of Cetuximab in vivo. These results show that TGFb is a key molecular determinant of resistance of cancers to EGFRtargeted therapy (52).…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the targeting of EGFR signaling by the EGFR antibody Cetuximab in a xenograft model of head and neck cancer resulted in emergence of resistant tumor cells that expressed relatively higher levels of TGFb and elevated levels of TGFb in the tumor microenvironment enable tumor cells to evade antibodydependent cell-mediated cytotoxicity and resist the antitumor activity of Cetuximab in vivo. These results show that TGFb is a key molecular determinant of resistance of cancers to EGFRtargeted therapy (52).…”
Section: Discussionmentioning
confidence: 76%
“…As for the new molecular determinants of resistance to anti-EGFR agents, proto-oncogene securin promotes resistance to gefitinib-induced apoptosis via an EGFRindependent pathway in human cancer cells (26) and TGFb provides an intrinsic EGFR-independent survival signal that protects squamous cancer cells from cetuximab-dependent cellular cytotoxicity (27). In this study, we observed that KITENIN was significantly highly expressed in tumor tissues from metastatic colorectal cancer patients with wild-type KRAS who showed poor responses to cetuximab/conventional chemotherapy after the initial stages of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Galunisertib has a well-defined therapeutic window based on dampening, but not shutting down, receptor signalling 164 and has shown clinical activity in a variety of solid tumour models. This and other TGFβ inhibitors have been tested in combination therapy in preclinical models, showing synergy with other therapeutic modalities such as chemotherapy 165 and growth factor inhibition 166 . In a transgenic mouse melanoma model, galunisertib showed synergistic activity with anti-CTLA4 therapy 167 .…”
Section: Killer Inhibitory Receptorsmentioning
confidence: 99%